Organización documental y su incidencia en la gestión administrativa de la Unidad Educativa Enrique Ponce Luque Cantón Quevedo año 2016. - Briones García, Ruth María (2016)
The research project has been carried out has components that can not be ignored when tending to draw general conclusions that interest us. The investigation was preceded by methodological elements that sometimes mistook the development of the search for a solution to the problem. We can conclude that there are indeed contradictory elements in the documentary organization process in the administration of the Education Unit Enrique Ponce Luque "we have an obligation to take over as the new elements that appear as results of observation and analysis that has been taken. One of the conclusions we can draw from this research is necessary to optimize the use of information using standards and documentary procedures to allow the organization and standardization of the files of the Education Unit Enrique Ponce Luque, there is no perfect organization but is They take into account the diversity of needs that may exist and the characteristics and related to the development of administrative management. It is however to find the maximum response, and the best solutions when confronting a documentary design organization.